2008
DOI: 10.12968/bjca.2008.3.10.31224
|View full text |Cite
|
Sign up to set email alerts
|

Communication skills training for nurses working with patients with heart disease

Abstract: This pilot project evaluated the feasibility, acceptability and effectiveness of a 3-day communication skills course for nurses working with patients with heart disease The outcomes were: the change in the nurses’ communication skills score from pre-course to 12 weeks post-course; the change in the nurses’ level of confidence in communicating with patients; the qualitative evaluation of the nurses views of the course for health professionals working with patients with heart disease. Ten self-selected British … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Harrison (2001) challenges healthcare workers for whom disclosure is uncomfortable and ‘none of [their] business’ (p. 143) to acknowledge that deferring acceptance of disclosed information is a barrier to health promotion. Wilkinson et al. (2008) found that the skills of 10% of participating nurses actually worsened or did not improve after participation in a communication skills course.…”
Section: Resultsmentioning
confidence: 99%
“…Harrison (2001) challenges healthcare workers for whom disclosure is uncomfortable and ‘none of [their] business’ (p. 143) to acknowledge that deferring acceptance of disclosed information is a barrier to health promotion. Wilkinson et al. (2008) found that the skills of 10% of participating nurses actually worsened or did not improve after participation in a communication skills course.…”
Section: Resultsmentioning
confidence: 99%
“…Although effective communication is a core competency for oncology nurses and a variety of CST models have been developed (Langewitz et al, 2010; Sheldon, 2011; van Weert et al, 2011; Wilkinson et al, 2008), a module specifically designed to train oncology nurses on how to communicate issues surrounding end-of-life care has not yet been created. To address this key need, the researchers adapted an end-of-life care module (from the physician module) for oncology nurses.…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, a variety of interventions to improve nurses’ communication skills and efficacy has been developed. The majority of communication skills training (CST) has been effective at increasing nurses’ abilities to provide psychosocial support to patients, their confidence in handling conflicts and criticism, and communication-related self-efficacy (Langewitz et al, 2010; Sheldon, 2011; van Weert, Jansen, Spreeuwenberg, van Dulmen, & Bensing, 2011; Wilkinson, Linsell, Perry, & Blanchard, 2008). Most CST developed for nurses has focused on general communication, with participants focusing on how to have difficult conversations and break bad news (Baer & Weinstein, 2013).…”
mentioning
confidence: 99%
“…When the related literature was examined, it was observed that nurses had problems both with patients and physicians from time to time due to insufficient communication (13)(14)(15). It is stated that patients and their relatives feel emotionally better with the effectively established communication; on the other hand, when insufficient communication is established, those receiving care experience uncertainty and dissatisfaction and they feel anxious (16). The pediatric nurse has roles such as prime caregiver, advocate, educator, researcher, manager, coordinator-collaborator and also consulting.…”
Section: Introductionmentioning
confidence: 99%